10-Year Historical Development of Dual Layer Hollow Fiber Hemodialysis Membranes (Journal of Applied Membrane Science & Technology, 2023)
Hollow fiber membranes have been employed to purify blood from within the heart of hemodialysis process, namely dialyzer. In the past 10 years, the interest on the utilization of dual layer hollow fiber (DLHF) membranes has arisen due to the innovative idea of combining adsorption and diffusion processes into one step. This short review outlines the historical development of DLHF hemodialysis membranes that spans from year 2012 to year 2022. The motivation and the outcome from the first and the second generation DLHF hemodialysis membranes are discussed. In addition, the use of DLHF membranes in other hemodialysis-related application is presented. This short review would provide a perspective for membranologists to recognize the issues in DLHF hemodialysis membranes and to work their way to finding the real solutions.
Keywords: Dual layer hollow fiber, hemodialysis, mixed matrix membrane, adsorption process, diffusion process